Clinical and economic implications of focal dissection treatment following percutaneous transluminal angioplasty of the superficial femoral artery: an exploratory analysis based on the TOBA II Study - Jan B Pietzsch; Benjamin P Geisler; Abigail M Garner; Anne M Ryschon; William A Gray; Masahiko Fujihara; Peter A Schneider (Journal of Comparative Effectiveness Research)
Aim: Percutaneous transluminal angioplasty (PTA) for peripheral artery disease (PAD) commonly leads to dissections which are associated with higher target lesion revascularization (TLR) rates. Clinical and economic consequences of dissection management in the femoropopliteal artery following PTA, and specifically the potential economic benefit of focal dissection repair using the novel Tack Endovascular System, remain unknown. Methods: A decision-analytic model was used to estimate 24-month clinical events, costs and quality-adjusted life year (QALY) gain for a Tack-supported versus status-quo PTA strategy. Patient and lesion characteristics and TLR rates were derived from the PTA cohort of the TOBA II clinical trial, an observational cohort, and literature. Cost–effectiveness was determined from a US payer and provider perspective separately for the non-severe (grade A or B), severe (grade C and higher) and the entire dissection cohort. Results: TLR rates were lower for the Tack-supported strategy compared with PTA (7.7 vs 27.4% in the non-severe, 13.9 vs 25.8% in the severe and 12.0 vs 26.3% in the entire dissection cohort). Cost and QALY differences were +$297/ + 0.0110 in the non-severe dissection cohort and - $1602/ + 0.0067 in the severe dissection cohort, resulting in an incremental cost–effectiveness ratio (ICER) of $25,622 in the non-severe cohort and dominance in the severe cohort and the entire cohort. Conclusion: Compared with a ‘status-quo’ approach, proactive focal stenting may lead to fewer reinterventions and improved quality of life. There appears to be a graded economic benefit of focal dissection treatment, being cost-effective in non-severe dissections and even cost saving in severe dissections.